Encountering (cultural) nationalism, Islam and gender in the body politic of India - Runa Das (Social Identities, Volume 10, Number 3, 2004, 2004)
In this article, I analyse how the ideology of Hindutva has been manipulated by the contemporary Bharatiya Janata Party (BJP) government of India to locate an internal enemy along religious lines to support its nationalist agenda, with subsequent implications for gender. Following a brief introduction to the literature of nationalism, with special reference to nationalism as an `invented tradition' and the role of `ideology as doxa', I situate the case of post-colonial Indian nationalism whereby I highlight how a complexity of `social imaginaries' and `identities' have been used by the post-colonial Indian state leaders as constituting the `mental state' of India. I contrast the conceptions of a political/territorial nationalism as evidenced under the Congress with that of the emerging Hindu/cultural nationalism under the contemporary BJP and highlight how the BJP, like the colonialists but with subtle differences, has sought to replay the re-construction of Islam/Indian Muslims as Others to the supposedly Hindu India. Interweaving feminism to support its nationalist project becomes an integral part of the BJP's nationalist/communalist agenda.